Interoperability and Standards: The Way for Innovative Design in Networked Working Environments - Agostinho, C.; Almeida, B.; Nuñez-Ariño, M. J.; Jardim-Gonçalves, R. (Cranfield University Press, 2009)
In today’s networked economy, strategic business partnerships and outsourcing has become the dominant paradigm where companies focus on core competencies and skills, as creative design, manufacturing, or selling. However, achieving seamless interoperability is an ongoing challenge these networks are facing, due to their distributed and heterogeneous nature. Part of the solution relies on adoption of standards for design and product data representation, but for sectors predominantly characterized by SMEs, such as the furniture sector, implementations need to be tailored to reduce costs. This paper recommends a set of best practices for the fast adoption of the ISO funStep standard modules and presents a framework that enables the usage of visualization data as a way to reduce costs in manufacturing and electronic catalogue design.
Organised by: Cranfield University
Keywords: Interoperability; Modular Architectures; Morphisms; Standards; Visualization